(untitled) (Vietnam Journal of Community Medicine, 2026)
To describe factors related to the duration of labor from Stage IB to Stage III in full-term primiparous women delivering vaginally at Hai Duong Obstetrics and Gynecology Hospital. Subjects and Methods:A cross-sectional descriptive study was conducted on all full-term primiparous women delivering vaginally at Hai Duong Obstetrics and Gynecology Hospital during November 2022 to January 2023 who met the sampling criteria. Results and Conclusion: The average maternal age was 25.69 years, with the majority (44%) aged 20–25 years. The highest proportion of women (45%) weighed 60–70 kg, while the majority (62%) had a height between 150–160 cm. The mean gestational age was 39.42 weeks. Several factors were found to be related to labor duration, including maternal age, anteroposterior conjugate diameter, fetal weight, biparietal diameter, amniotic membrane status, and amniotic fluid index. These factors showed statistically significant differences with p < 0.05.